1985
DOI: 10.1021/bi00340a035
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR spectroscopy of sulfmyoglobin

Abstract: The 1H NMR spectra of ferrous sulfmyoglobin, metsulfmyoglobin, and ferric cyanosulfmyoglobin were obtained at 300 MHz. Hyperfine-shifted resonances are observed in the case of metsulfmyoglobin and ferric cyanosulfmyoglobin that have line widths and cover a chemical shift range that are comparable to the corresponding forms of normal myoglobin. Two methyl resonances are observed in the spectrum of ferric cyanosulfmyoglobin at 44.19 and 25.48 ppm (25 degrees C, pH 8.3) that have been assigned to heme methyls at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…NMR experiments indicate that the 4-vinyl group of the heme is not necessary for the initial formation of the S A sulfheme isomer, though clearly this group is required for formation of the S C sulfheme isomer. [20][21][22][23][24]28,61,62 Thus, the electronic properties of the sulfheme adduct, specifically the changes in the pyrrolic β ring, have a considerable effect on the energy of the heme HOMO orbitals modulating the separation energy between the a 1u and a 2u orbitals. 60 S A , S B , and S C Sulfheme Electronic Excitations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR experiments indicate that the 4-vinyl group of the heme is not necessary for the initial formation of the S A sulfheme isomer, though clearly this group is required for formation of the S C sulfheme isomer. [20][21][22][23][24]28,61,62 Thus, the electronic properties of the sulfheme adduct, specifically the changes in the pyrrolic β ring, have a considerable effect on the energy of the heme HOMO orbitals modulating the separation energy between the a 1u and a 2u orbitals. 60 S A , S B , and S C Sulfheme Electronic Excitations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that oxygen binding to sulfMb and to sulfHb was reduced, in relation to the normal heme proteins, by ∼2500 and ∼135 times, respectively. The presence of an analogous sulfur chlorin ring in sulfheme has been supported by the three-dimensional structure of cyanomet-sulfmyoglobin, resonance Raman, NMR, hemoglobin I mutants from Lucina pectinata , catalase, , and lactoperoxidase (LPO) . There are heme proteins that do not form sulfheme such as hemoglobin I (HbI) from L. pectinata , which has Gln64 in the E7 position.…”
Section: Introductionmentioning
confidence: 99%
“…Michel et al showed the formation of an analogous compound upon interaction of Mb-O 2 with H 2 S and termed the complex sulfmyoglobin (sulfMb) [2527]. These derivatives have a sulfur atom incorporated in the heme pyrrole B with a characteristic optical band around 620 nm [26, 2831]. The displacement of the band depends on heme-Fe oxidation and ligation states, as well as the type of the sulfheme isomer [26, 32–34].…”
Section: Interaction Of H2s With Myoglobin and Hemoglobinmentioning
confidence: 99%
“…Using labeled sulfur ( 35 S) experiments it was first determined that only one atom of sulfur was incorporated into the heme group of sulfMb [26–28, 44, 46]. Later, proton NMR studies of sulfMb identified the sulfur atom on pyrrole B by analyzing the chemical shifts of the heme 1,3,5,8-methyls and the 2,4-vinyl substitutions [31, 34, 47]. Based on NMR and resonance Raman data it was then proved that the sulfur atom is incorporated across the double β-β bond of pyrrole B either as episulfide or thiochlorin, with a heme-chlorin type structure [26, 28, 30, 31, 34, 44, 47, 48].…”
Section: Interaction Of H2s With Myoglobin and Hemoglobinmentioning
confidence: 99%
See 1 more Smart Citation